Neutrophilic noncoding RNAs predict outcomes of acute ischemic stroke patients treated with recombinant tissue plasminogen activator - Han, Ziping; Li, Lingzhi; Tao, Zhen; Wang, Rongliang; Zhao, Haiping; Zheng, Yangmin; Yang, Zhenhong; Zhong, Liyuan; Fan, Junfen; Luo, Yumin (Frontiers in Pharmacology, 2022)
There’s no evidence demonstrating the association between noncoding RNAs levels before IV recombinant tissue plasminogen activator (rtPA) administration and the outcomes of acute ischemic stroke (AIS). 146 AIS patients received rtPA treatment were recruited at the stroke center from 2018 to 2019, and 103 patients were included in this study. A panel of noncoding RNAs (miRNA-23a, miRNA-193a, miRNA-128, miRNA-99a, miRNA-let-7a, miRNA-494, miRNA-424, and lncRNA H19) were measured in the circulating neutrophils of AIS patients before rtPA treatment. Endpoints included excellent outcome (modified Rankin Scale score [mRS] 0-1) or poor outcome (mRS > 1) at 3 months and symptomatic intracerebral hemorrhage (sICH) after rtPA treatment. Among the eight noncoding RNAs detected in circulating neutrophils of the 103 participants, miRNA-23a levels were associated with the stroke severity on admission and symptom progression at 24h after rtPA treatment. A noncoding RNA score composed of miRNA-23a, miRNA-99a, and lncRNA H19 was screened to predict the functional outcome at 3 months and the incidence of sICH after rtPA treatment. In the logistic regression analysis, the noncoding RNA score ≥ -0.336 (OR = 2.862 [1.029-7.958], p = 0.044) was an independent predictor of the poor outcome at 3 months after adjustment of clinical variables, the addition of the noncoding RNA score to the clinical model improved the discrimination (IDI% = 4.68 [0.65–8.71], p = 0.020), as well as the net reclassification (NRI% = 33.04 [0.54–71.49], p = 0.016). The noncoding RNA score ≥ -0.336 (OR = 5.250 [1.096-25.135], p = 0.038) was also independently predicted the sICH, the addition of the noncoding RNA score to the clinical variables improved discrimination and reclassification as well. The noncoding RNA score was also associated with the infarct volume and symptom improvement at 7 days after rtPA treatment. In conclusion, a higher neutrophilic noncoding RNA score provides predictive value to identify AIS patients with worse outcomes after rtPA treatment. miRNA-23a, miRNA-99a, and lncRNA H19 are worth further investigation for their effects in thrombolysis after AIS.